الإنتقال من النتيجة المحاسبية الى النتيجة الجبائية دراسة حالة مؤسسة مطاحن الأغواط 2015 - بلمشري عبد الجليل; عثمان محمد عز الدين; نبق قويدر (جامعة عمار ثليجي الاغواط, 2022)
This research aims to clarify how to move from the accounting result to the tax result. The study also summarized the tax systems followed by Algeria and the most important deferred taxes that are determined from the two results represented in the tax on corporate profits and deferred taxes that appear due to the difference between the financial accounting system and thealgerian taxation system. We dropped the study on the Laghouat Mills Corporation and concluded that there is an integrative relationship between the accounting result and the tax result, and that the tax result is nothing but the accounting result with the introduction of some changes and amendments to it in accordance with the tax laws and legislation.